Monozygotic twins with familial hypercholesterolemia and high lipoprotein(a) levels leading to identical cardiovascular outcomes: Case report and review of the literature - Meral Kayıkçıoğlu; Hakan Gökalp Uzun; Aslı Tetik Vardarlı; Lale Tokgözoğlu (KARE Publishing, 2020)
Homozygous familial hypercholesterolemia (HoFH) is a rare, autosomal dominant disease that leads to premature cardiovascular disease (CVD). Since monozygotic twins share the intrauterine environment and have the same age and gene profile, they could represent a very special resource for the investigation of the causes and the natural course of FH. This report is a description of 36-year-old monozygotic twin brothers with almost identical early coronary artery involvement due to FH concomitant with high lipoprotein(a) (Lpa) levels and a review of the literature. Sequence analysis revealed that the twins were homozygous for the LDLR c.1060+10G>A (rs12710260) mutation and heterozygous for the LDLR c.542C>T (rs557344672) mutations. Both were also homozygous for the c.1060+7T>C (rs2738442) and c.1586+53A>G (rs1569372) mutations in the LDLR gene as well as c.4265A>T (rs568413) mutations in the APOB gene. In the literature, there are 7 twin cases with reported FH, but none with high Lpa levels. The HoFH twins in this case report had lower low-density lipoprotein (LDL) cholesterol levels than expected (before treatment 204 and 223 mg/dL), with almost identical coronary involvement. Both had an extremely high Lpa level (308 and 272 nmol/L) with a very low coronary calcium score (16 AU) and a good response to statins (>60%). There was a history of the first CVD event occurring at nearly the same age (32-34 years) in the family. This could be an important aspect of FH families as a result of the similar timing of cumulative LDL exposure exceeding the threshold of CVD events. In conclusion, this first report of monozygotic HoFH twins with elevated Lpa levels and almost identical early coronary artery involvement at the same age provides evidence to substantiate the hypothesis of lifetime cholesterol burden/exposure.